2019
DOI: 10.1186/s13104-019-4741-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial and fungal contamination of kitchens of Birjand University of Medical Sciences

Abstract: ObjectiveThis study aims to evaluate the total bacterial and fungal count of tools, devices and surfaces of kitchens of the centers affiliated to Birjand University of Medical Sciences. In this study, 200 samples from four kitchens of Birjand University of Medical Sciences were obtained. After the preparation of serial dilutions, samples were cultured in plate count agar (PCA) plates and Sabouraud dextrose agar (SDA). After incubation at 37 and 25 °C for 24–48 and 72–96 h respectively, the microbial and fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…Total bacteria, fungal counts, coliform, and Lactobacillus were analyzed separately by the pour plate technique as described by Karami et al (2017), Rahimi et al (2019), andSingh et al (2013) with slight modification. Briefly, 1 g of homogenized relish products was mixed with 9 ml of sterile peptone salt (LOBA Chemie, India) and vortexed for 5 min.…”
Section: Microbial Determination Of Relish Productsmentioning
confidence: 99%
“…Total bacteria, fungal counts, coliform, and Lactobacillus were analyzed separately by the pour plate technique as described by Karami et al (2017), Rahimi et al (2019), andSingh et al (2013) with slight modification. Briefly, 1 g of homogenized relish products was mixed with 9 ml of sterile peptone salt (LOBA Chemie, India) and vortexed for 5 min.…”
Section: Microbial Determination Of Relish Productsmentioning
confidence: 99%
“…Cross contamination is widely known to play an important role in the transmission of foodborne disease. In the study conducted by Rahimi, Ebrahimi, Barikbin, and Zeinali (2019), the transfer of microorganisms directly from contaminated foods, such as fresh vegetables and incompletely washed meat, was suspected to be the cause of the high contamination of devices such as refrigerators in hospital kitchens. de Jong, Verhoeff‐Bakkenes, Nauta, and de Jonge (2008) have reported that high levels of microbial contamination are often observed in salads when cross‐contamination via hands is not prevented and often can be reduced by appropriate hand‐washing protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The homogenate was gradient-diluted with sterile saline, and 100 μL of suspension was added to the count agar plate. After being cultured at 37 °C for 48 h, the number of single colonies was calculated …”
Section: Materials and Methodsmentioning
confidence: 99%
“…After being cultured at 37 °C for 48 h, the number of single colonies was calculated. 38 Statistical Analysis. The SPSS v22.0 software (IBM Corporation, Armonk, NY, USA) was used for statistical analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%